Analysis of the marketing communications and strategy of Contours fitness - Merta, Jonáš; Horová, Olga; Hochman, Jiří; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
The thesis analyzes marketing communication of Contours fitness by using theoretical background. The aim of the thesis is theoretical description and analysis of communication tools. Based on situational analysis the thesis evaluates the effectivness of communication mix and suggest measures to its optimalization. The outcome of the thesis is theoretical description of communication mix of the company, newly established communication objectives and analysis of communication tools with emphasis on communication effectivness.
Vedoucí práce: Olga Horová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses